Caribbean Report 14-01-1999 - The British Broadcasting Corporation; Richards, Ken (anchor); Owen, Arthur (interviewee); Gibbs, Tom (correspondent); Derycke, Eric (interviewee); Orr, Carol (correspondent); Parkinson, Byron (interviewee); Richards, Ken (correspondent); Croft, Colin (interviewee); Hughes, Dominic (correspondent); Alibhai-Brown, Yasmin (interviewee); Halveston, John (interviewee); et al. (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Ken Richards (00:00-00:26) 2. The governing Barbados Labour Party (BLP) relists its Manifesto for the upcoming general elections. Key initiatives from the BLP’s 1999 Manifesto include Prime Minister Owen Arthur’s vision for the economic and social transformation of Barbados, eradicating poverty, promoting a single market economy in CARICOM and developing a strategic political relationship with the OECS . Bertram Niles reports (00:27-02:44 ) 3. Colombian President Andres Pastrana is scheduled to visit Havana to seek assistance from Fidel Castro in brokering peace talks with left wing guerilla factions in Colombia. Pastrana views this visit as a top priority for his five month old administration. Castro is well respected by the guerillas and perceived as a regional peace broker in some quarters. Populist Venezuelan President elect Hugo Chavez will join the discussions. Belgium Foreign Affairs Minister Erik Derycke is also in Cuba to host talks with President Castro about the release of a single European currency, the Euro, and the impact on the Cuban economy. Tom Gibbs reports (02:45 –06:00) 4. The majority of schools across Jamaica remained closed following a two-day island strike staged by teachers. Teachers are pressing for increases in materials and equipment allowance. The Jamaican government has offered marginal increases in material and equipment allowances, uniform, laundry and motor car loans. These concessions have been dismissed by the Jamaica Teachers Association President Bryon Parkinson. Parkinson when interviewed stated that some of the allowances would only benefit select teaching personnel. The Ministry of Labour issued an invitation for all teachers to attend a meeting for conciliatory talks. Carol Orr reports on the level of public support for the teachers (06:01 – 07:46) 5. The West Indies is hoping to salvage some Caribbean pride by attempting to win the fifth and final test against South African. The South Africans have won four of the five match series and ...